Team and system performance : a case study of two ABC projects - Abu Mansor, Nur Naha; Pike, Richard; Tayles, Mike (Faculty of Management and Human Resource Development, 2006)

(untitled)
Recent literature has shown a renewed interest in implementation of information system implementation research. Current trends in the organisational deployment of IS tools have motivated new studies of Activity Based Costing (ABC) implementation efforts. This paper reports on two case study investigation of ABC system project. An interview schedule of 13 ABC team members’ and users’ experiences developing ABC systems and user perceptions of ABC performance is highlighted and compared. A preliminary case of ABC implementation in the two ABC projects will be discussed. Engineers, accountants, and senior executives were interviewed across the 2 ABC projects in the organisation. Interview instrument, based on previously validated measurement of ABC team and user experience through questionnaires were adapted and validated to suit the interview questions. The results revealed that both ABC projects had team members that were highly cohesive in nature, and with very high conflict resolution ability. ABC performance was deemed successful and effective as perceived by their users in areas of cost accuracy and increased dollar improvements. However, these effects were rather minimal and yet to be justified over time. Nevertheless, overall ABC users across the two ABC projects revealed that there were positive impacts of ABC felt by its implementation. This paper is intended to share two ABC projects implementation experience in the organisation. It is hoped, to shed light on various team and performance problems that future consideration for ABC innovation